Effect of community-based education on undergraduate nursing students' skills: a systematic review - Arezoo Zeydani; Foroozan Atashzadeh-Shoorideh; Fatemeh Abdi; Meimanat Hosseini; Sima Zohari-Anboohi; Victoria Skerrett (BMC, 2021)
Abstract Background Community-based education, as an effective approach to strengthen nurses' skills in response to society's problems and needs has increased in nursing education programs. The aim of this study was to review the effect of community-based education on nursing students' skills. Methods For this systematic review, ProQuest, EMBASE, Scopus, PubMed/ MEDLINE, Cochran Library, Web of Science, CINAHL and Google Scholar were searched up to February 2021. The methodological quality of the studies was assessed using the Mixed Methods Appraisal Tool (MMAT). Seventeen studies were included in this systematic review. Inclusion criteria included articles published in English and were original articles. Results In all studies, undergraduate nursing students' skills were improved by participation in a community-based education program. Community-based education enhances professional skills, communication skills, self-confidence, knowledge and awareness, and critical thinking skills and teamwork skills in undergraduate nursing students. Conclusions Community-based education should be used as an effective and practical method of training capable nurses to meet the changing needs of society, to improve nurses 'skills and empower them to address problems in society.